Fiscal Trap Gabon Economy Case Study - Bidzo, Médard Mengue (DEMO, 2016)
Th e persistence of the economic and fi nancial crisis present in Greece teaches that the combination of an increase in the tax rate with austerity in periods of recession creates a vicious circle where if connected decrease in tax revenues, reduced gross domestic product and increase public debt ratio on GDP. Th is mechanism is known as the fi scal trap. Th anks to the generalized moments method in system (MMG), we verifi ed this hypothesis for the Gabonese economy.(original abstract)